TASK1 (K2P3.1) K+ channel inhibition by endothelin-1 is mediated through Rho kinase-dependent phosphorylation - Seyler, Claudia; Duthil-Straub, Elvenn; Zitron, Edgar; Gierten, Jakob; Scholz, Eberhard P.; Fink, Rainer; Karle, Christoph; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (British journal of pharmacology, 2012)
BACKGROUND AND PURPOSE: TASK1 (K2P3.1) two-pore-domain K+ channels contribute substantially to the resting membrane potential in human pulmonary artery smooth muscle cells (hPASMC), modulating vascular tone and diameter. The endothelin-1 (ET-1) pathway mediates vasoconstriction and is an established target of pulmonary arterial hypertension (PAH) therapy. ET-1-mediated inhibition of TASK1 currents in hPASMC is implicated in the pathophysiology of PAH. This study was designed to elucidate molecular mechanisms underlying inhibition of TASK1 channels by ET-1. EXPERIMENTAL APPROACH: Two-electrode voltage clamp and whole-cell patch clamp electrophysiology was used to record TASK1 currents from hPASMC and Xenopus oocytes. KEY RESULTS: ET-1 inhibited TASK1-mediated IKN currents in hPASMC, an effect attenuated by Rho kinase inhibition with Y-27632. In Xenopus oocytes, TASK1 current reduction by ET-1 was mediated by endothelin receptors ETA (IC50= 0.08 nM) and ETB (IC50= 0.23 nM) via Rho kinase signalling. TASK1 channels contain two putative Rho kinase phosphorylation sites, Ser336 and Ser393. Mutation of Ser393 rendered TASK1 channels insensitive to ETA- or ETB-mediated current inhibition. In contrast, removal of Ser336 selectively attenuated ETA-dependent TASK1 regulation without affecting the ETB pathway. CONCLUSIONS AND IMPLICATIONS: ET-1 regulated vascular TASK1 currents through ETA and ETB receptors mediated by downstream activation of Rho kinase and direct channel phosphorylation. The Rho kinase pathway in PASMC may provide a more specific therapeutic target in pulmonary arterial hypertension treatment.